Online-Offline Identity as a Representation of Cyber Culture in the Academic Community - Syahid Sudrajat, Mochammad (International Journal on Higher Education Issues, 2025)
Social media with many varieties no longer has user segmentation. Mc Luhan's famous phrase about the medium is the message and the global village is finally answered. That there is no message in the media that does not contain a meaning and that no message is distributed without the intent / purpose. In the case of social media, these messages are distorted to be more than just meanings. It has been transformed into a waste of information due to the overlapping of the same information. Message producers and message consumers become biased. While the identity of users of social media continues to change due to the mingling of behavior, community and reality between the virtual and the real. This research tries to see the unique phenomena that occur due to communication patterns that are intertwined in cyberspace and the real world so as to form an online-offline identity. Cyber culture that occurs in the academic environment becomes more varied due to the need for identity in cyberspace and in the real world. Social media is a place to look for identity or just throw away information for nothing. By combining the concept of cyber culture and the communication map of the cyber community on social media, online-offline identity representations can be identified.